Ways of Analyzing Teaching Quality: Potentials and Pitfalls - Blikstad-Balas, Marte; Klette, Kirsti; Tengberg, Michael (Quality in Nordic Teaching, 2022)
Recent research suggests that there is a direct link between quality of teaching and teacher’s instructions and student achievement scores. Additionally, there is a strong correlation between levels of teaching quality and differences between schools and classrooms. However, measuring teaching quality has proven to be difficult and scholars strive to decide on the what and the how when aiming to measure teaching quality. This book discusses the many dilemmas of measuring teaching quality, be it substantial, theoretical, or methodological. This edited volume presents eight chapters, assigned authors provide updated and new knowledge on the many challenges linked to defining what teaching quality is and how it can be measured. This collection of chapters originates from the discussions at the QUINT Conference 2019: Analysing Teaching Quality: Perspectives, Potential, and Pitfalls, organized by the Nordic Centre of Excellence: Quality in Nordic Teaching 18-20 June 2019 at the University of Oslo.